Hypertension and Dizziness: is there a Relation? - V. A. Parfenov; T. M. Ostroumova; O. D. Ostroumova (Столичная издательская компания, 2019)
One of the most frequent complaints of patients with hypertension (HT) is dizziness. Dizziness is understood as a variety of subjective sensations that patients define as "dizziness" - a sense of instability when walking, the illusion of rotation of surrounding objects, the feeling of approaching fainting, the inability to concentrate, and "fog" in the head. Experts share the systemic dizziness (vertigo) and non-systemic. The causes of vertigo in most cases are diseases of the inner ear (Meniere's disease, benign paroxysmal positional vertigo [BPPV], vestibular neuronitis. The most common form of dizziness is psychogenic dizziness. In the vast majority of cases, HT is not the cause of dizziness. The most common cause of vestibular (systemic) dizziness in patients with HT, as in the general population, is BPPV, and the most common cause of non-systemic dizziness is psychogenic dizziness. Among other causes of dizziness in patients with HT should be kept in mind too fast and/or intensive lowering of blood pressure, rhythm and conduction disorders, orthostatic hypotension (especially in elderly and senile patients in the presence of concomitant diabetes).